Genome-scale single-cell mechanical phenotyping reveals disease-related genes involved in mitotic rounding. Issue 1 (December 2017) - Toyoda, Yusuke; Cattin, Cedric; Stewart, Martin; Poser, Ina; Theis, Mirko; Kurzchalia, Teymuras; Buchholz, Frank; Hyman, Anthony; Müller, Daniel
Abstract To divide, most animal cells drastically change shape and round up against extracellular confinement. Mitotic cells facilitate this process by generating intracellular pressure, which the contractile actomyosin cortex directs into shape. Here, we introduce a genome-scale microcantilever- and RNAi-based approach to phenotype the contribution of > 1000 genes to the rounding of single mitotic cells against confinement. Our screen analyzes the rounding force, pressure and volume of mitotic cells and localizes selected proteins. We identify 49 genes relevant for mitotic rounding, a large portion of which have not previously been linked to mitosis or cell mechanics. Among these, depleting the endoplasmic reticulum-localized protein FAM134A impairs mitotic progression by affecting metaphase plate alignment and pressure generation by delocalizing cortical myosin II. Furthermore, silencing theDJ-1 gene uncovers a link between mitochondria-associated Parkinson's disease and mitotic pressure. We conclude that mechanical phenotyping is a powerful approach to study the mechanisms governing cell shape. During cell division animal cells generate intracellular pressure and round against their environment, but the genes responsible for this are largely unknown. Here the authors use a microcantilever- and RNAi-based assay to screen > 1000 genes and identify 49 genes involved in mitotic cell rounding; many are novel to this process.